2020
DOI: 10.1094/mpmi-06-20-0138-r
|View full text |Cite
|
Sign up to set email alerts
|

NADPH Oxidase ClNOX2 Regulates Melanin-Mediated Development and Virulence in Curvularia lunata

Abstract: The role of NADPH oxidases (NOXs) in pathogenesis and development in the Curvularia leaf spot (CuLS) agent Curvularia lunata remains poorly understood. In this study, we identified C. lunata ClNOX2, which localized to the plasma membrane and was responsible for reactive oxygen species (ROS) generation. Scavenging the ROS production inhibited the conidial germination and appressorial formation. The ClNOX2 and ClBRN1 deletion mutants were defective in 1,8-dihydroxynaphthalene (DHN) melanin accumulation, appresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Previous study showed that ClNOX2 subunit functioned on intracellular O 2 •− /H 2 O 2 generation, and mainly regulated melanin‐mediated development and virulence in C . lunata (Wang et al ., 2020a). To investigate the roles of other four putative NOX subunits in C .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous study showed that ClNOX2 subunit functioned on intracellular O 2 •− /H 2 O 2 generation, and mainly regulated melanin‐mediated development and virulence in C . lunata (Wang et al ., 2020a). To investigate the roles of other four putative NOX subunits in C .…”
Section: Resultsmentioning
confidence: 99%
“…During plant–fungus interactions, NOXs regulate the formation of specialized infection structures such as appressoria, the infection peg and invasive hyphae (Egan et al ., 2007; Nordzieke et al ., 2019; Ryder et al ., 2013). NOXs negatively regulate cell wall permeability and integrity for phytopathogenic fungus penetrating the host cell wall (Wang et al ., 2020a). Although the role of NOXs in fungal sexual reproduction and host infection has been well studied, the precise regulatory mechanisms remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, melanized sclerotia of S. sclerotiorum and B. cinerea are essential for vegetative growth [ 25 , 32 ], and the level of melanin accumulation is often inversely proportional to the fungal biomass. That is, a decrease in melanin is often associated with increased hyphal growth [ 89 ]. A function of PKS9 in the maintenance of vegetative growth was supported by the investigation of a larger population of strains in this study, indicating that the expression of VdPKS9 was significantly upregulated in AH-type but not in the MH-type under normal growth, and in later developmental stages (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…NOXs play important roles in many biological processes in living cells. In filamentous fungi, the NOX-derived ROS regulate many aspects of the life cycle including vegetative hyphal growth, conidiation, secondary metabolism, and pathogenicity of many phytopathogenic fungi ( Egan et al., 2007 ; Giesbert et al., 2008 ; Segmüller et al., 2008 ; Heller and Tudzynski, 2011 ; Tudzynski et al, 2012 ; Ryder et al., 2013 ; Wang et al., 2020 ). Unlike that in M. oryzae and some other phytopathogenic fungi, here we found that knockout of CgnoxA or CgnoxB did not influence the colony morphology or growth rate ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The appressoria generate high turgor and physical force to rupture plant cuticle and form a penetration peg which develops into invasive hyphae to penetrate plant tissue ( De Jong et al., 1997 ; Ryder and Talbot, 2015 ). In addition, NOXs are involved in appressorium formation in several phytopathogenic fungi ( Ryder and Talbot, 2015 ; Wang et al., 2020 ). The expression pattern assay of CgnoxA , CgnoxB , and CgnoxR showed that CgnoxB was significantly up-regulated in the appressoria ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%